Task variations for backtrack - Menyhárt, László; Zsakó, László (Teaching Mathematics and Computer Science, 2021)
This article has been written for informatics teachers who want to issue back-track based tasks on their lessons or as homework or on competitions. We present a few methods to generate a more complicated problem from a simpler task, which will be more complex, and its solution needs a good idea or trick. Starting from an example, we lead the reader through increasingly di cult task variations. Subject Classification: 97P50